The death of urbanism. Transitions through five stages of grief. - White, Marcus; Langenheim, Nano (Spurbuchverl., 2019)
Koolhaas pronounced urbanism dead in 1995. Since then, urban design has struggled to come to terms with this and other losses including environmental stability, affordable housing, design control, and urban amenity. This book explores urban design paradigms transitioning through a misappropriation of Kübler-Ross’ “five stages of grief” – from pro-sprawl ‘denial’, NIMBY ‘anger’, revisionist new urbanist ‘bargaining’, ‘depressed’ starchitects, through to an optimistic manifesto of ‘acceptance’. Marcus White (PhD) is an award-winning architect and urban designer, Professor of Urban Design at Swinburne University of Technology, and director of Harrison and White. Nano Langenheim is a landscape architect, horticulturist, arborist, and lecturer in landscape architecture and urban design at the University of Melbourne. Their research explores the integration of data, emerging technology and cultural specificity to support design decision making for cities in transition.
Keywords: Stadtsoziologie; Urbanismus; Stadtentwicklungskonzept; Paradigmenwechsel; Stadtgestaltung; Nachhaltige Stadtentwicklung; Architekturtendenz; Architekturauffassung